Pengembangan Instumen Discharge Planning dengan Metode Experiental Learning pada Pasien Diabetes Melitus - Nuritasari, Rahayu Tri; Kurdaningsih, Septi Viantri; Tarisa, Tarisa; Riyadi, Muhammad Ilham Rasyid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aimed to develop a discharge planning instrument based on experiental learning theory. The Research method uses a Research and Development with interview, document reciew and observation. The results showed that the content standards were following SNARS but needed adjustments so that they were easily understood by healthworkers in implementation. The incomplete discharge planning documentation was because healthworkers lacks an understanding of the material that must be delivered. Interviews with health professionals (76%) nurses suggested guideline discharge planning, (65%) nurses recommended revision of instruments. Health education has been done by applying the experiental learning theory that involves the client and family, giving clients and families real experience and can apply it. Conclusion the instrument develope the adjustment of the items on the instrument at the beginning of the admission and when being treat as well as the addition of items when going to the discharge and the guideline in the form of application of educational material at each stage that can be use by healthworker so that discharge planning can be optimize. Keywords: Diabetes Melitus, Discharge Planning, Education, Experiental Learning, Instrument